Solution processed self-assembled monolayer gate dielectrics for low-voltage organic transistors - Ball,J; Wöbkenberg,PH; Colléaux,F; Kooistra,FB; Hummelen,JC; Bradley,DDC; Anthopoulos,TD (2008)
Low-voltage organic transistors are sought for implementation in high volume low-power portable electronics of the future. Here we assess the suitability of three phosphonic acid based self-assembling molecules for use as ultra-thin gate dielectrics in low-voltage solution processable organic field-effect transistors. In particular, monolayers of phosphonohexadecanoic acid in metal-monolayer-metal type sandwich devices are shown to exhibit low leakage currents and high geometrical capacitance comparable to previously demonstrated self-assembled monolayer (SAM) type dielectrics [1, 2] but with a higher surface energy. The improved surface energy characteristics enable processing of a wider range of organic semiconductors from solution. Transistors based on a number of solution-processed organic semiconductors with operating voltages below 2 V are also demonstrated. © 2009 Materials Research Society.